To What Extent Is the Institutional Environment Responsible for Worldwide Differences in Economic Development - Mariusz Próchniak (Contemporary Economics)
This study aims to assess to what extent the institutional environment is responsible for worldwide differences in economic development. To answer this question, a new concept of the institutions-augmented Solow model is constructed. The analysis covers 153 countries and the period 1994-2009. The empirical analysis confirms a large positive impact of the quality of the institutional environment on the level of economic development. This positive link has been evidenced for all six of the employed institutional indicators (although nonlinearities are present in some cases). Our own concept of the institutions-augmented Solow model fits the empirical data very well. It turns out that differences in physical capital, human capital and the institutional environment (which is measured by the governance indicator) explain approximately 75% of the differences in economic development among the countries of the world. According to the institutions-augmented Solow model, the production function that is consistent with the empirical data is Y = K0.372H0.315L0.313Q0.705, where K is the physical capital, H is the human capital, L is the labor and Q represents the institutional indicator.